Reduction of leakage current and power in full subtractor using MTCMOS technique - Gautam, M.; Akashe, S. (2013 International Conference on Computer Communication and Informatics, 2013)
In this paper a full subtractor using MTCMOS technique design is proposed. Combinational logic has extensive applications in quantum computing, low power VLSI design and optical computing. Reducing power dissipation is one of the most principle subjects in VLSI design today. But Scaling causes sub threshold leakage currents to become a large component of total power dissipation. Low-power design techniques proposed to minimize the active leakage power in nanoscale CMOS very large scale integration (VLSI) systems. Using MTCMOS approach compare leakage current and leakage power of full subtractor in active mode. leakage current in conventional full subtractor is 228.7 fA and proposed full subtractor is 271.1 fA, reduction in current is 15.63%. simulation result is performed at 0.7 volt using cadence virtuoso tool in 45 nanometer technology.